C81 CORRECTION OF MASSIVE TRICUSPIDAL INSUFFICIENCY WITH PERCUTANEOUS TRICLIP SYSTEM IN WOMAN WITH MARFAN'S SYNDROME. (18th May 2022) - De Remigis, F; Benvenuto, M; Tomassoni, G; Lavorgna, A; De Rosa, M; Fabiani, D; Napoletano, C
Abstract: The interventional–percutaneous therapy of valve pathologies has undergone, in recent years, an enormous technological development in traditional surgery. In particular, the recent introduction for the percutaneous treatment of tricusp insufficiency allows you to correct forms otherwise not surgically treatable. We report a case of a 58–year–old woman suffering from Marfan's Sd with massive tricuspidal insufficiency in relation to valve leaf prolapse, complicated by retrograde heart failure and recurrent episodes of atriale flutter, Anamnestic cardiovascular hystory began at the age of 38 (2000) when patient underwent to the first cardiac surgery in emergency contest, with replacement of the ascending aorta and aorto–coronary bypass for acute dissection (type A); after one year (2002) perform surgery to replace the aortic arch with reimplantation of the neck vessels; at the age of 45 (2009) she underwent aortic valve replacement surgery with mechanical prosthesis, for severe aortic valve insufficiency; finally, at the age of 48 (2012) she underwent surgery to replace the thoraco–abdominal aorta and reimplantation of the abdominal vessels for chronic dissecting aneurysm. Given the high risk of re–surgery for tricuspid valve repair/replacement, the Heart–Team has indicated the percutaneous correction of tricuspid insufficiency using the valve clip. The procedure was performed under general anesthesia, ultrasound–guided with transesophageal; three clips were placed at the level of the commissure between the anterior flap and septal flap with the final result of an 80% reduction in the degree of tricuspid insufficiency, absence of peri and post procedural complications; discharge of the patient on day 3. The follow–up was completed at six months: asymptomatic patient, significant reduction of arrhythmic episodes, absence of peripheral venous stasis, reduction of hepatomegaly; echocardiographic control showed persistence of optimal alignment of the clips in the closing rim of the anterior and septal tricuspid flap; normal volume and function of the right ventricle, absence of indirect signs of hypertension in the small circulation, to report a significant reduction in arrhythmic events (two episodes of atrial flutter treated effectively with drug therapy).